ANTIPROLIFERATIVE EFFECT OF Dendrophthoe pentandra EXTRACTS TOWARDS HUMAN BREAST ADENOCARCINOMA CELLS (MCF-7) (Jurnal Teknologi (Sciences & Engineering), 2015)
Dendrophthoe pentandra (DP) is a semi-parasitic plant. Previous studies showed that this plant possessed diverse medicinal properties. The present study was carried out to determine antiproliferative activity of various DP crude extracts. Extracts of petroleum ether, diethyl ether, chloroform, ethyl acetate and methanol, have been evaluated through IC50 value, which defined by the concentration of drug that is required for the inhibition of 50% of cell population in vitro. The determination of percentage cell viability was conducted by using MTT assay. The screening assay involved the use of malignant cell line MCF-7 (breast cancer cell) whereas the normal cell line was L929 (connective cell). The control drug used was tamoxifen. The ethyl acetate and methanol extracts were found to be more effective against MCF-7 cancer cell lines compared to the others. All extracts showed no remarkable effect against normal cell L929 with IC50 values more than 100 Âµg/mL. In contrast to tamoxifen, all extracts showed less cytotoxicity effect towards normal cells. The data obtained from this study provide notable preliminary information on the cytotoxic/antiproliferative effect of different DP extracts and further study should be carried out to isolate the active compound of the most potential DP extracts.
Keywords: Dendrophthoe pentandra; extracts; antiproliferative; MCF-7 cells; MTT